Matte painting 2 : d'artiste : digital artists master class. - Uesugi, Yusei, ....-; Dennison, Max, ....-; Thunig, Chris, ....- (Adelaide : Ballistic, 2011)
In this volume, Yusei Uesugi, Max Dennison, and Chris Thunig provide you with priceless matte painting techniques to improve your skills. The book covers the process from concept right through to painting and 3-D techniques and tricks, to the completion of complex environments-including the famous Coruscant sequence from Star Wars: Episode III-Revenge of the Sith.